Superiority of mosapride citrate to picosulfate sodium as a laxative for withdrawal from regular enemas in children with severe functional constipation - Fujii, Yoshimitsu; Kouhata, Eriko; Kaneko, Kazunari (Indian Journal of Child Health, 2021)
Background: Severe functional constipation (FC) with low bowel movement frequency (BMF) of ?1 day/week and hard stools oftenrequires regularly repeated enemas or often leads to enema dependency (ED). Aim: The current study aimed to compare the efficacy of mosapride citrate (Mo) with the traditional stimulant laxative picosulfate sodium (Pi) for withdrawal from ED in children with severe FC. Results: Twenty-four treatment-naïve patients who met the Rome IV diagnostic criteria for FC seen at our center for 8 years from 2012 were enrolled. Glycerin enema was repeated until the BMF was ?3.5 days/week. Simultaneously, Mo at 0.3 mg/kg/day (n=11) or Pi at 0.25 mg/kg/day (n=13) was administered concomitantly with magnesium oxide or lactulose. The proportion of withdrawal from ED was significantly higher in the Mo group than Pi group during the 4 months observational period (90.9% vs. 46.2%, respectively; p=0.034) and shorter in time to withdraw from ED (0 vs. 3.5 months, respectively; p=0.015). Conclusion: Mo is more effective than Pi for withdrawal from ED in children with severe FC.